EXPERIMENTAL STUDY AND ANALYSIS OF FLAT BELT CONVEYER SYSTEM USING D.C. MOTOR DRIVE - Beg, Aiman; jaiswal, Narendra (International Journal of Engineering Technologies and Management Research, 2018)
In this paper, we are studying the flat belt conveyor system using of D.C. motor with various speed, in this way we are used the 12 V. D.C. motor, flat belt which having 2mm thickness, speed controller, inlet container and outlet container for the purpose of finding the maximum material handling rate with speed.